Assessing the integration of the Sustainable Development Goals (SDGs) in business sustainability management - Wong, Jia Ci (2021)
The Sustainable Developments Goals (SDGs) are imperative from both environmental and social aspects, as well as for the long-term financial sustainability of a firm. Contextually, there might be various internal and external determinants influencing firms’ willingness to implement and reveal the SDGs activities. This study specifically investigates the influence of firm size and financial performance, ownership structure, corporate governance and industry affiliation on adoption, extent and comprehensiveness of SDGs engagement by embracing a multi-theoretical framework. Based on data from FTSE Bursa Malaysia Top 100 (FBM100) Index constituents, the findings indicate the level of business awareness on the SDGs is fulfilling expectations with prosperous related developments gaining the most attention. However, it can be observed that firms seem reluctant to integrate the SDGs into broad business strategy. By employing both logistic and multiple regression analyses, the alignment of the SDGs in business sustainability management is found to be significantly related to firm size and leverage. Impacts of ownership structure namely ownership concentration and government ownership are found to be modest. Additionally, boards with larger size and a great extent of non-executive directors are more likely to embrace the SDGs in a systematic and measurable manner. In contrast to what was anticipated, there is no evidence for a coherent industry membership effect in the SDGs integration. These findings can serve as an incentive for the private sector, especially from developing countries, to intensify the level of SDGs integration into their plans and operations.